(untitled) (Zaporizhzhia Historical Review, 2021)
The article is analyzed attitudes to idea of convocation Ukrainian Parliament in 1919-1920 by main ukrainian political parties in the period of Durektoria UNR. The author shows mail political reasons, which had an influence on party’s position in this issue.